Aplikasi Teknologi Realiti Maya Dalam Pembelajaran Untuk Matapelajaran Fizik KBSM - Norlelawati, Abdul Aziz (2002)

(untitled)
Since thirty years ago, computer has become a part of the necessity in a classroom. The main role of it is to transmit the learning process through a system in which recognized as Pengajaran, Pembelajaran, Berbantukan Komputer(PBK). Though there are so many PBK softwares have been built, but they still have weaknesses especially in the methods or techniques of teaching and learning process. Most of the softwares are basically based on the drilling approach. Though they have succeeded in drilling the counting and language skills, this methodology has not yet able to present complex concepts successfully. Most of the systems are teacher-centered and do not follow the real teaching and learning process. The techniques of' artificial intelligence and multimedia starts to be recognized and used in the educational field. It has provide the probability to build the learning environment in which does not exist in previous traditional systems. This thesis will discuss on the concept of virtual reality as well as the software for Physic learning. It covers the topics of electromagnet and energy from the syllabus of Form 4 and Form 5 in secondary school. This multimedia software approach will produce more interesting and better presentation as it is able to use the combination of 3D objects, texts and graphics in the same application.